Integrated Marketing Communication for Agricultural Tourism using the Brand Archetypes: A Case Study of Phato District, Chumphon Province - Sawagvudcharee, Ousanee (JOURNAL OF SOUTHERN TECHNOLOGY, 2024)
Agritourism plays a significant role in the tourism industry. However, the challenge has been the lack of integrated marketing communication (IMC) that can effectively represent the unique identity and local brands of agritourism. These brands are created to improve tourism business by allowing tourists to be aware of, recognize, experience them emotionally and psychologically. The researcher is interested in studying the creation of IMC for agricultural tourism using the brand archetypes, with Phato District, Chumphon Province as a case study. The district was selected for its interesting community enterprise group in charge of promoting fruit quality, natural environment, strong agricultural culture, and fame on agricultural tourism. Data were collected from document sources, and semi-structured interviews were used to supplement the document data. Content analysis, critical and thematic analysis were applied. Findings revealed that creating IMC to convey the brand archetypes of agricultural tourism in the area should involve a more analytical approach. This requires delving deep into information related to local agricultural culture that allows a close connection between the brands and consumers. Only then, the brand personality can be conveyed to foster brand recognition, repeat purchases, and long-term sustainability in agritourism.